Risk‐based Regulation in Continental Europe? Explaining the Corporatist Turn to Risk in German Work Safety Policies. (September 2015) - Paul, Regine; Huber, Michael
Abstract : While having gained relevance in Anglo‐Saxon scholarly and political debates, risk‐based regulation seems to be a stranger to continental European settings. The more fragmented and often corporatist forms of decision making in countries such as Germany have been identified as key obstacles to a risk‐based rationalization of policy interventions. Based on an in‐depth case study of German work safety policies, this article nuances this account theoretically and empirically. It argues, firstly, that current risk‐based regulation studies suffer from a systemic bias toward the competition‐oriented forms of regulation so widely spread in the Anglo‐Saxon world. They thereby misread the dynamics and rationalities of alternative regulatory approaches elsewhere in Europe. Secondly, as our policy analysis shows, this is especially true of corporatist and self‐regulatory forms of policymaking, which characterize the case of German work safety. Rather than impeding the adoption of risk‐based regulation, corporatist arrangements bear distinct structural features that render risk tools attractive. This finding goes beyond the scope of contemporary risk‐based regulation scholarship. Unlike claimed for the Anglo‐Saxon context, hopes of efficiency and effectiveness are not boosters for risk‐based approaches in corporatist work safety policy arrangements. Instead, risk tools serve the structural need to sustain trust relationships, rationalize consensus finding, and promote solidarity within self‐regulatory settings. We conclude that a corporatist type of risk‐based regulation needs to complement the existing competition‐based type to account for the spatial, functional, and ideological diversity of empirical cases of risk‐based regulation. We also propose the first advances toward such a new research agenda, highlighting most importantly the necessity to trace the emergence and dynamics of specific types of risk‐based regulation in research frameworks which can surmount national essentialism.